An evolution of a financial planning in Poland in the years 1945–1990 - Michał Jędrzejczyk (Prawo Budżetowe Państwa i Samorządu)
Advantages of a multiannual financial planning have been noticed in Poland since the 1960’s. First attempts to provide a long-term financial planning took place in Poland in 1961–1965 (at that time this planning referred to local budgets financial planning). However, in the above-mentioned period forecasted amounts of income and spending limits were considered as unrealistic and they were not coordinated with the state budget. In addition, the need to ground local budgets on their own income was more and more clearly evident as ideas regarding the multiannual financial planning have been developed. It should be noted that it was already in 1961–1965 when attempts were made to answer first fundamental questions regarding the choice of the concept of the multiannual planning. Hence, discussion between supporters of the centralized “top-down” and persons who supported the local “bottom-up” multiannual financial planning deserve special attention in this article. Despite a political situation at that time it was noticed that the concept of local budgets’ multiannual financial planning (prepared according to the “bottom-up” model) is more effective than the government’s multiannual financial planning (which is implemented without an involvement of a so-called civic factor).